Engineering a sustainable chrome-free leather processing based on novel lightfast wet-white tanning system towards eco-leather manufacture. (1st February 2021) - Shi, Jiabo; Zhang, Ruizhen; Mi, Zhiyuan; Lyu, Siqi; Ma, Jianzhong
Abstract: Wet-white tanning system for chrome-free leather processing has been deemed as a feasible alternative from the source to effectively eliminate potential environmental and human health risks of conventional chrome tanning. This work presents a novel sustainable chrome-free leather processing based on lightfast wet-white tanning system of hydrolysable Tara tannins synergized with synthetic clay nanoplatelets (Laponite) and active aluminium salts (Lutan @ BN). The results show that the introduction of BN can significantly enhance the hydrothermal stability of wet-white leathers. The novel wet-white tanning system selected as 10% Tara–1% Laponite–3% BN for 2 h can endow the wet-white leathers with a shrinkage temperature ( T s ) above 95 °C. Moreover, Tara–Laponite–BN complexes can be in-situ formed on the surface of the collagen fibers or between collagen fibrils within the collagen fiber strands, stabilizing primary and conformational structures of the collagens. Notably, the incorporation of BN within the collagens can increase the isoelectric point (IEP) of the leather matrix and facilitate exhaustions of anionic post-tanning chemicals in chrome-free leather processing. The resultant leather exhibits pleasant pastel color, favorable light-fastness, and reasonable physical performances without containing restricted hazardous Cr(VI) and free formaldehyde in accordance with current Chinese standard requirements for furniture leather and European Union Eco-label criteria. These results will provide more perspectives for designing and rationalizing sustainable chrome-free leather processing towards eco-leather manufacture. Graphical abstract: Image 1 Highlights: A novel sustainable chrome-free leather processing has been developed. The introduction of aluminium salts enhances exhaustions of anionic chemicals. The resulting chrome-free leather exhibits improved physical properties.